Developing modelling lenses among practicing teachers. Issue 5 (3rd July 2016) - Shahbari, Juhaina Awawdeh; Tabach, Michal
Abstract : Growing awareness of the importance of modelling activities in mathematics education has raised the question of whether teachers are prepared to facilitate the engagement of students in such activities. The current study investigates the effects of how teachers cope with modelling activities in developing their abilities to identify modelling cycles. The research was conducted among 34 practicing teachers studying for master's degrees at a college of education. The data were collected from two reports and one reflection provided by the participants about a modelling activity conducted by a group of five sixth-grade students. The first report was submitted before the participants themselves dealt with the modelling activities, while the second report and the reflection were submitted after their participation in the modelling activities. The findings indicate that prior to participating in the activity most of the teachers described the students' participation in modelling activity as a linear process. The participating teachers noticed the final mathematical model and the mathematical results obtained from applying the model, but most of them ignored the realistic results, the validating process and the cyclical nature of the mathematical model's progress. However, after the practicing teachers participated in modelling activities as learners, their reports indicated that most were able to recognize all the modelling phases and to distinguish the cyclical processes of the progress of the mathematical models. Moreover, according to the analyses of the reflections, the participating teachers are aware of the changes in their descriptions.